Kajian pemanfaatan limbah ampas tahu dan sekam padi dengan perekat tapioka menjadi briket biomassa - Baihaqi, Muhammad; Masjud, Yunita Ismail (Journal of Earth Kingdom, 2024)
Energy is a crucial requirement for the survival of humans. The increasing demand for energy necessitates the exploration of alternative, renewable energy options. One potential avenue is the utilization of biomass energy from waste tofu residue to produce briquettes. Rice husk is chosen as an additive to enhance the calorific value of the briquettes. The objective of this research is to identify the properties of briquettes made from tofu residue and rice husk, including moisture content, ash content, volatile matter, and calorific value, in accordance with the standard (SNI–01-6235–2000). Briquettes are produced by combining tofu residue, rice husk, and tapioca flour in three variations: 30:20:17:33, 25:25:17:33, and 20:30:17:33, respectively. The research results, using ANOVA analysis, indicate that the composition of the mixture variations significantly affects the parameters of moisture content, ash content, volatile matter, and calorific value in laboratory tests. Furthermore, t-Test analysis reveals that the parameters that significantly meet the briquette standard according to SNI–01-6235–2000 are moisture content and calorific value. In conclusion, the composition of briquette mixture variations influences the test results, and the moisture content parameter significantly complies with the briquette standard according to SNI–01-6235–2000. However, ash content, volatile matter, and calorific value parameters do not yet meet the briquette standard according to SNI–01-6235–2000. Therefore, utilizing tofu residue as a renewable energy source in the form of briquettes could be considered, with some aspects requiring further refinement to meet the standard.